Developing a New First Nations Health Governance System: Creation of an Independent, First Nations Run Organization - Alexander Ryan Levesque (McMaster University Library Press, 2017)
In 2011 a tripartite agreement between the province of British Columbia (BC), Health Canada, and First Nations leaders created the First Nations Health Authority (FNHA): a unique approach to First Nations health governance. The creation of the FNHA came after almost ten years of discussion and agreements between the three parties. The goal of the FNHA is to address health disparities between First Nations and other residents of BC, as well as increase the voice of First Nations people in the health system. The issues that led to the creation of the FNHA came onto the government's agenda due to an increased knowledge of the health crises facing BC First Nations, and a growing interest throughout Canada in increasing First Nations autonomy and input. In 2013 Health Canada transferred authority over all First Nations health programming to the FNHA, with the hope that an independent, First Nations run organization would better address the health-related needs of First Nations people.  While evaluation of the FNHA is limited presently, since it only released its first five-year plan just over a year ago, a 2015 report by the Auditor General gives some insight into how the FNHA is functioning. If the FNHA can overcome a few weaknesses and threats to its stability, it has the potential to guide First Nations self-determination with respect to health care in Canada. En 2011, une entente tripartite entre le gouvernement provincial de la Colombie-Britannique (C.-B.), Santé Canada, et les leaders des Premières Nations de la C.-B. a créé la First Nations Health Authority (FNHA) : une approche unique pour la gestion de la santé les Premières Nations. La FNHA a été créée après presque dix ans de discussion et accords entre les trois groupes. L'objectif de la FNHA est d'éliminer les disparités en matière de santé entre des Premières Nations et les autres résidents de la C.-B., et aussi d'augmenter la voix des Premières Nations dans le système de santé. Les questions qui ont mené à la création de la FNHA sont apparues sur l'agenda du gouvernement en raison d'une conscience accrue des crises sanitaires auxquelles sont confrontées les Premières Nations de la C.-B. et un intérêt croissant pour l'autonomie et l'apport des Premières Nations.  En 2013, Santé Canada a transféré l'autorité sur l'ensemble des programmes de santé des Premières Nations dans l'espoir qu'une organisation indépendante dirigée par les Premières Nations réponde mieux aux besoins des membres des Premières Nations. Alors que l'évaluation de la FNHA est limitée en ce moment, puisqu'elle a récemment publié son premier plan quinquennal, un rapport du vérificateur général de 2015 a donné un aperçu de la façon dont fonctionne la FNHA. Si la FNHA peut surmonter quelques faiblesses et doutes à sa stabilité, elle peut guider l'autodétermination des Premières Nations en matière de soins de santé au Canada.